Adoption and welfare impacts of multiple agricultural technologies: evidence from eastern Zambia. (5th July 2018) - Khonje, Makaiko G.; Manda, Julius; Mkandawire, Petros; Tufa, Adane Hirpa; Alene, Arega D.
Abstract: Using plot level panel data and multinomial endogenous switching regression, this article analyzes the adoption and welfare impacts of multiple agricultural technologies in eastern Zambia. We adapt a multinomial endogenous switching/treatment effect regression framework to correct for selection bias and endogeneity originating from both observed and unobserved heterogeneity. Results indicate that joint adoption of multiple agricultural technologies had greater impacts on crop yields, household incomes, and poverty than the adoption of individual components of the technology package. Our findings suggest that efforts aimed at raising household incomes and reducing poverty should focus on promoting the adoption of multiple agricultural technologies through provision of improved support services such as extension and input supply.